Design of sEMG assembly to detect external anal sphincter activity: a proof of concept. (31st October 2017) - Shiraz, Arsam; Leaker, Brian; Mosse, Charles Alexander; Solomon, Eskinder; Craggs, Michael; Demosthenous, Andreas
Abstract: Objective : Conditional trans-rectal stimulation of the pudendal nerve could provide a viable solution to treat hyperreflexive bladder in spinal cord injury. A set threshold of the amplitude estimate of the external anal sphincter surface electromyography (sEMG) may be used as the trigger signal. The efficacy of such a device should be tested in a large scale clinical trial. As such, a probe should remain in situ for several hours while patients attend to their daily routine; the recording electrodes should be designed to be large enough to maintain good contact while observing design constraints. The objective of this study was to arrive at a design for intra-anal sEMG recording electrodes for the subsequent clinical trials while deriving the possible recording and processing parameters. Approach : Having in mind existing solutions and based on theoretical and anatomical considerations, a set of four multi-electrode probes were designed and developed. These were tested in a healthy subject and the measured sEMG traces were recorded and appropriately processed. Main results : It was shown that while comparatively large electrodes record sEMG traces that are not sufficiently correlated with the external anal sphincter contractions, smaller electrodes may not maintain a stable electrode tissue contact. It was shown that 3 mm wide and 1 cm long electrodes with 5 mm inter-electrode spacing, in agreement with Nyquist sampling, placed 1 cm from the orifice may intra-anally record a sEMG trace sufficiently correlated with external anal sphincter activity. Significance : The outcome of this study can be used in any biofeedback, treatment or diagnostic application where the activity of the external anal sphincter sEMG should be detected for an extended period of time.